Experimental study on mechanical behavior of welded joints of strain strengthening austenitic stainless steel under 77K. Issue 4 (April 2021) - Si, Jun; Ren, Facai; Ren, Bin
Abstract: With the development of economy and technology, people's demand for material properties is developing towards the extreme direction of cryogenic temperature and high pressure. The development of materials with better properties has been widely studied. Austenitic stainless steel S30408 is a typical transformation induced plastic steel, that is, the martensite produced after strain affects the mechanical properties of the material, which will improve the yield strength of the material, effectively reduce the wall thickness. Compared with base metal, welded joint is the weakest link in pressure vessel. Therefore, the research on the mechanical properties of the welded joint of strain strengthening austenitic stainless steel can effectively ensure the safety and reliability of the strain strengthening pressure vessel. In this paper, experimental study on mechanical properties of S30408 welded joints with strain-strengthening were carried out.